Input of DNA Microarrays to Identify Novel Mechanisms in Multiple Myeloma Biology and Therapeutic Applications - Mahtouk, Karène; Hose, Dirk; Vos, John de; Moreaux, Jérôme; Jourdan, Michel; Rossi, Jean François; Rème, Thierry; Goldschmidt, Hartmut; Klein, Bernard (Clinical cancer research, 2007)
Multiple myeloma is a B-cell neoplasia characterized by the proliferation of a clone of malignant plasma cells in the bone marrow. We review here the input of gene expression profiling of myeloma cells and of their tumor microenvironment to develop new tumor classifiers, to better understand the biology of myeloma cells, to identify some mechanisms of drug sensitivity and resistance, to identify new myeloma growth factors, and to depict the complex interactions between tumor cells and their microenvironment. We discuss how these findings may improve the clinical outcome of this still incurable disease.
Gesehen am 21.01.2022